Socio-Sufism of Orang Maiyah: Toward Human Sovereignity in Togetherness - Rizqa Ahmadi (Al-Albab, 2017)
Among various religious groups in Indonesia is Orang Maiyah (Gathering Community) that has become a unique phenomenon. Cak Nun (Emha Ainun Najib) is the central figure in the community as well as the source of knowledge and inspiration for its members (although in so many occasion Cak Nun refuses to be called so). This paper explores the style of social Sufism teachings attached to the community approached by descriptive qualitative analysis. This work shows that Orang Maiyah, which is spread in various regions of Indonesia, has become a religiously motivated movement that brings people together to achieve a "sovereigned human" state of life. Cak Nun is not a sole magnet that lures the community members. The members of the community have a freedom to choose the paths of truth according to their own conscience through dialogue, discussion. They also exchange information from various sources provided by the Maiyah activities.